The Morality of Universal Respect - Dias, Maria Clara (Analysis. Journal of Philosophical Research, 2018)
In this article I intend to present the moral of universal respect and its commitment to a conception of egalitarian justice. For this, I intend to clarify what it means, according to Tugendhat, to justify a concept of morality, and, more specifically, to accept the moral of universal respect. For the author, the question of accepting or not a moral perspective is related to the question of the type of person we want to be, to construction of our qualitative identity. With this, Tugendhat discards the possibility of responding to the so-called moral skepticism and proposes the substitution of the promise of an ultimate foundation of morality, by the justification of the greater plausibility of a moral perspective, against competing moral perspectives. Promoting a re-reading of the Kantian moral principle as the best expression of our moral demand, Tugendhat will defend our commitment to a concept of equal justice and respect for the basic rights of all individuals.